Highly acidic phytase from Aspergillus niger NCIM 563 under submerged fermentation - Soni, S. K.; Khire, Jayant Malhar (FEBS Journal, 2006)
31st Congress of the Federation-of-European-Biochemical-Societies (FEBS), Istanbul, TURKEY, JUN 24-29, 2006

Production of lactic acid and fructose from media with cane sugar using mutant of Lactobacillus delbrueckii NCIM 2365 - Patil, S. S.; Kadam, S. R.; Patil, S. S.; Bastawade, Kulbhushan B.; Khire, Jayant Malhar; Gokhale, D. V. (Letters in Applied Microbiology, 2006)
Aims: To examine the potential of Lactobacillus delbrueckii mutant, Uc-3 to produce lactic acid and fructose from sucrose-based media. Methods and Results: The mutant of L. delbrueckii NCIM 2365 was cultivated in shake flask containing hydrolysed cane sugar (sucrose)-based medium. The lactic acid yield and volumetric productivity with hydrolysed cane concentration up to 200 g l(-1) were in the range of 92-97% of the theoretical value and between 2.7 and 3.8 g l(-1) h(-1), respectively. The fructose fraction of the syrup produced was more than 95% when the total initial sugar concentration in the medium was higher (150-200 g l(-1)). There are no unwanted byproducts detected in the fermentation broth. Conclusions: We demonstrated that L. delbrueckii mutant Uc-3 was able to utilize glucose preferentially to produce lactic acid and fructose from hydrolysed cane sugar in batch fermentation process. Significance and Impact of the Study: These findings will be useful in the production of lactic acid and high fructose syrups using media with high concentrations of sucrose-based raw materials. This approach can lead to modification of the traditional fermentation processes to obtain value-added byproducts, attaining better process economics.
Keywords: fructose accumulation; hydrolyzed cane sugar; lactic acid production; Lactobacillus delbrueckii; Mutant

Purification, characterization and substrate specificity of thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) - Gote, M. M.; Khan, Mohammad Islam; Gokhale, D. V.; Bastawade, Kulbhushan B.; Khire, Jayant Malhar (Process Biochemistry, 2006)
An extracellular thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) has been purified to homogeneity by chromatographic step, using Phenyl Sepharose CL-4B column. The specific activity of the enzyme was increased approximately 389-fold, from 1.03 U/mg protein to 400 U/mg protein. The molecular mass of the purified enzyme as determined by SDS-PAGE and gel filtration was 79.9 and 165.9 kDa, respectively, suggesting dimeric nature. The purified alpha-galactosidase is a non-glycosylated protein with a pI of 4.9. The pH and temperature optima for the purified enzyme are 6.5-7.0 and 65 degrees C, respectively. The alpha-galactosidase is stable over a broad pH range (3-9) and its half-life of inactivation (t(1/2)) at 70 degrees C is 30 min. The partial N-terminal sequence of alpha-galactosidase showed remarkable homology (80% similarity) with earlier reported alpha-galactosidase from B. stearothermophilus NUB 3621. The secondary structure of the enzyme determined by circular dichroism (CD) spectroscopy exhibited alpha/beta class of protein and showed temperature induced conformational forms below and above the transition temperature. The purified enzyme showed biphasic Arrhenius plot with break point at 55 degrees C for pNPG and 50 degrees C for melibiose, raffinose and stachyose. The enzyme hydrolyzes alpha-1-3, alpha-1-4, and alpha-1-6 galactosidic linkages and not the beta-galactosidic linkages. Synthetic substrates pNPG and oNPG had lower K-m and higher K-cat as compare to natural substrates, melibiose, raffinose, and stachyose. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha-galactosidase; Bacillus stearothermophilus (NCIM-5146); Purification; Secondary structure; thermostable enzyme

Active site directed chemical modification of alpha-galactosidase from bacillus stearothermophilus (NCIM 5146): involvement of lysine, tryptophan and carboxylate residues in catalytic site - Gote, M. M.; Khan, Mohammad Islam; Khire, Jayant Malhar (Enzyme and Microbial Technology, 2007)
The catalytic amino acid residues of the extracellular a-galactosidase (alpha-D-galactoside galactohydrolase; EC 3.2.1.22) from Bacillus stearothermophilus NCIM 5146 were investigated by pH dependence and chemical modification studies. These results suggested that carboxylate and a lysine residue take part in catalysis and only lysine residues were essential for substrate binding. Carbodiimide mediated chemical modification of the enzyme also supported that a carboxylate residue located in the active site act as a nucleophile base in substrate cleavage. Acylation and reductive methylation of lysine residues by acetic, citraconic anhydride and sodium borohydride suggested that four protonated lysine residues carrying positive charge on its epsilon-amino group provides the positive charge density for binding of the substrate. Additionally four tryptophan residues also found near to the active site and in a moderately hydrophobic environment. Kinetic and thermal inactivation study of modified enzyme indicated that these tryptophan residues might have a role in the catalytic site as well as in the thermal stabilization of active site conformation at higher temperature. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Active site; alpha-galactosidase; Bacillus stearothermophilus; carboxylate; Chemical modification; lysine; Tryptophan

Production and partial characterization of two types of phytase from aspergillus niger NCIM 563 under submerged fermentation conditions - Soni, Sarvesh Kumar; Khire, Jayant Malhar (World Journal of Microbiology & Biotechnology, 2007)
Novel extracellular phytase was produced by Aspergillus niger NCIM 563 under submerged fermentation conditions at 30 degrees C in medium containing dextrin and glucose as carbon sources along with sodium nitrate as nitrogen source. Maximum phytase activity (41.47 IU/mL at pH 2.5 and 10.71 IU/mL at pH 4.0) was obtained when dextrin was used as carbon source along with glucose and sodium nitrate as nitrogen source. Nearly 13 times increase in phytase activity was observed when phosphate in the form of KH2PO4 (0.004 g/100 mL) was added in the fermentation medium. Physic-chemical properties of partially purified enzyme indicate the possibility of two distinct forms of phytases, Phy I and Phy II. Optimum pH and temperature for Phy I was 2.5 and 60 degrees C while Phy II was 4.0 and 60 degrees C, respectively. Phy I was stable in the pH range 1.5-3.5 while Phy II was stable in the wider pH range, 2.0-7.0. Molecular weight of Phy I and Phy II on Sephacryl S-200 was approximately 304 kDa and 183 kDa, respectively. Phy I activity was moderately stimulated in the presence of 1 mM Mg2+, Mn2+, Ca2+ and Fe3+ ions and inhibited by Zn2+ and Cd2+ ions while Phy II activity was moderately stimulated by Fe3+ ions and was inhibited by Hg2+, Mn2+ and Zn2+ ions at 1 mM concentration in reaction mixture. The Km for Phy I and II was 3.18 and 0.514 mM while Vmax was 331.16 and 59.47 mu mols/min/mg protein, respectively.
Keywords: Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation

Influence of pretreatment of agriculture residues on phytase production by aspergillus niger NCIM 563 under submerged fermentation conditions - Bhavsar, Kavita P.; Shah, Parin; Soni, Sarvesh Kumar; Khire, Jayant Malhar (African Journal of Biotechnology, 2008)
The extracellular phytase production by Aspergillus niger NCIM 563 was evaluated in medium containing various agriculture residues under submerged fermentation conditions. Phytase production was affected by inorganic phosphate content of agriculture residues which ranged from 2.8 to 8 mg/g. The agriculture residues containing less than 4 mg/g inorganic phosphate supported phytase production with maximum activity of 68 IU/ml in medium containing 1% rice bran on 11(th) day of fermentation. Addition of glucose up to 5% in fermentation medium containing 1% rice bran, enhanced phytase production. Pretreatment of agriculture residues with water to remove excess inorganic phosphate has significantly enhanced the phytase activity in case of de-oiled rice bran, wheat bran, peanut cake (low and high oil) and coconut cake. Maximum increase of 20.3 times in phytase activity was observed in case of wheat bran as compared to de-oiled rice bran, coconut cake, peanut cake high and low oil in which the increase in phytase activity was 6.85, 6.1, 5.3 and 3.0 times, respectively. Maximum phytase activity of 68 IU/ml was produced on the 11(th) day of fermentation compared to earlier reported 41.47 IU/ml phytase activity on the 15(th) day of submerged fermentation using 5% dextrin and 2.5% glucose, thus increasing productivity.
Keywords: Agriculture residue; Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation

Utilization of molasses sugar for lactic acid production by lactobacillus delbrueckii subsp delbrueckii mutant Uc-3 in batch fermentation - Dumbrepatil, Arti; Adsul, Mukund G.; Chaudhari, Shivani; Khire, Jayant Malhar; Gokhale, Digambar V. (Applied and Environmental Microbiology, 2008)
Efficient lactic acid production from cane sugar molasses by Lactobacillus delbrueckii mutant Uc-3 in batch fermentation process is demonstrated. Lactic acid fermentation using molasses was not significantly affected by yeast extract concentrations. The final lactic acid concentration increased with increases of molasses sugar concentrations up to 190 g/liter. The maximum lactic acid concentration of 166 g/liter was obtained at a molasses sugar concentration of 190 g/liter with a productivity of 4.15 g/liter/h. Such a high concentration of lactic acid with high productivity from molasses has not been reported previously, and hence mutant Uc-3 could be a potential candidate for economical production of lactic acid from molasses at a commercial scale.

Strain improvement and up scaling of phytase production by aspergillus niger NCIM 563 under submerged fermentation conditions - Shah, P.; Bhavsar, Kavita P.; Soni, S. K.; Khire, Jayant Malhar (Journal of Industrial Microbiology & Biotechnology, 2009)
Combination of physical and chemical mutagenesis was used to isolate hyper secretory strains of Aspergillus niger NCIM 563 for phytase production. Phytase activity of mutant N-1 and N-79 was about 17 and 47% higher than the parent strain. In shake flask the productivity of phytase in parent, mutant N-1 and N-79 was 6,181, 7,619 and 9,523 IU/L per day, respectively. Up scaling of the fermentation from shake flask to 3 and 14 L New Brunswick fermenter was studied. After optimizing various fermentation parameters like aeration, agitation and carbon source in fermentation medium the fermentation time to achieve highest phytase activity was reduced considerably from 14 days in shake flask to 8 days in 14 L fermenter. Highest phytase activity of 80 IU/ml was obtained in 1% rice bran-3.5% glucose containing medium with aeration 0.2 vvm and agitation 550 rpm at room temperature on 8th day of fermentation. Addition of either bavistin (0.1%), penicillin (0.1%), formalin (0.2%) and sodium chloride (10%) in fermented broth were effective in retaining 100% phytase activity for 8 days at room temperature while these reagents along with methanol (50%) and ethanol (50%) confer 100% stability of phytase activity at 4A degrees C till 20 days. Among various carriers used for application of phytase in feed, wheat bran and rice bran were superior to silica and calcium carbonate. Thermo stabilization studies indicate 100% protection of phytase activity in presence of 12% skim milk at 70A degrees C, which will be useful for its spray drying.
Keywords: Agriculture residue; Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation

Bacterial biosurfactants, and their role in microbial enhanced oil recovery (MEOR) - Khire, Jayant Malhar (Biosurfactants, 2010)
Surfactants are chemically synthesized surface-active compounds widely used for large number of applications in various industries. During last few years there is increase demand of biological surface-active compounds or biosurfactants which are produced by large number of microorganisms as they exert biodegradability, low toxicity and widespread application compared to chemical surfactants. They can be used as emulsifiers, de-emulsifiers, wetting agents, spreading agents, foaming agents, functional food ingredients and detergents. Various experiments at laboratory scale on sand-pack columns and field trials have successfully indicated effectiveness of biosurfactants in microbial enhanced oil recovery (MEOR).

Purification and characterization of two distinct acidic phytases with broad pH stability from aspergillus niger NCIM 563 - Soni, S. K.; Magdum, A.; Khire, Jayant Malhar (World Journal of Microbiology & Biotechnology, 2010)
Aspergillus niger NCIM 563 produced two different extracellular phytases (Phy I and Phy II) under submerged fermentation conditions at 30A degrees C in medium containing dextrin-glucose-sodium nitrate-salts. Both the enzymes were purified to homogeneity using Rotavapor concentration, Phenyl-Sepharose column chromatography and Sephacryl S-200 gel filtration. The molecular mass of Phy I and II as determined by SDS-PAGE and gel filtration were 66, 264, 150 and 148 kDa respectively, indicating that Phy I consists of four identical subunits and Phy II is a monomer. The pI values of Phy I and II were 3.55 and 3.91, respectively. Phy I was highly acidic with optimum pH of 2.5 and was stable over a broad pH range (1.5-9.0) while Phy II showed a pH optimum of 5.0 with stability in the range of pH 3.5-9.0. Phy I exhibited very broad substrate specificity while Phy II was more specific for sodium phytate. Similarly Phy II was strongly inhibited by Ag(+), Hg(2+) (1 mM) metal ions and Phy I was partially inhibited. Peptide analysis by Mass Spectrometry (MS) MALDI-TOF also indicated that both the proteins were totally different. The K (m) for Phy I and II for sodium phytate was 2.01 and 0.145 mM while V (max) was 5,018 and 1,671 mu mol min(-1) mg(-1), respectively. The N-terminal amino acid sequences of Phy I and Phy II were FSYGAAIPQQ and GVDERFPYTG, respectively. Phy II showed no homology with Phy I and any other known phytases from the literature suggesting its unique nature. This, according to us, is the first report of two distinct novel phytases from Aspergillus niger.
Keywords: Aspergillus niger; Phytase; Phytate; Poultry feed; Purification

Strain improvement of lactobacillus lactis for d-lactic acid production - Joshi, D. S.; Singhvi, M. S.; Khire, Jayant Malhar; Gokhale, D. V. (Biotechnology Letters, 2010)
Three mutants, isolated by repeated UV mutagenesis of Lactobacillus lactis NCIM 2368, produced increased d-lactic acid concentrations. These mutants were compared with the wild type using 100 g hydrolyzed cane sugar/l in the fermentation medium. One mutant, RM2-24, produced 81 g lactic acid/l which was over three times that of the wild type. The highest d-lactic acid (110 g/l) in batch fermentation was obtained with 150 g cane sugar/l with a 73% lactic acid yield. The mutant utilizes cellobiose efficiently, converting it into d-lactic acid suggesting the presence of cellobiase. Thus, this strain could be used to obtain d-lactic acid from cellulosic materials that are pre-hydrolyzed with cellulase.
Keywords: Cellobiose utilization; D-Lactic acid production; Lactobacillus lactis; Mutant; Sucrose (cane sugar)

High level phytase production by aspergillus niger NCIM 563 in solid state culture: response surface optimization, up-scaling, and its partial characterization - Bhavsar, Kavita P.; Kumar, V. Ravi; Khire, Jayant Malhar (Journal of Industrial Microbiology & Biotechnology, 2011)
Phytase production by Aspergillus niger NCIM 563 was optimized by using wheat bran in solid state fermentation (SSF). An integrated statistical optimization approach involving the combination of Placket-Burman design (PBD) and Box-Behnken design (BBD) was employed. PBD was used to evaluate the effect of 11 variables related to phytase production, and five statistically significant variables, namely, glucose, dextrin, NaNO(3), distilled water, and MgSO(4)center dot 7H(2)O, were selected for further optimization studies. The levels of five variables for maximum phytase production were determined by a BBD. Phytase production improved from 50 IU/g dry moldy bran (DMB) to 154 IU/g DMB indicating 3.08-fold increase after optimization. A simultaneous reduction in fermentation time from 7 to 4 days shows a high productivity of 38,500 IU/kg/day. Scaling up the process in trays gave reproducible phytase production overcoming industrial constraints of practicability and economics. The culture extract also had 133.2, 41.58, and 310.34 IU/g DMB of xylanase, cellulase, and amylase activities, respectively. The partially purified phytase was optimally active at 55A degrees C and pH 6.0. The enzyme retained ca. 75% activity over a wide pH range 2.0-9.5. It also released more inorganic phosphorus from soybean meal in a broad pH range from 2.5 to 6.5 under emulated gastric conditions. Molecular weight of phytase on Sephacryl S-200 was approximately 87 kDa. The K (m) and V (max) observed were 0.156 mM and 220 mu m/min/mg. The SSF phytase from A. niger NCIM 563 offers an economical production capability and its wide pH stability shows its suitability for use in poultry feed.
Keywords: Aspergillus niger; Phytase; Response surface optimization; Solid state fermentation; Statistical methods

Downstream processing of extracellular phytase from aspergillus niger: chromatography process vs. aqueous two phase extraction for its simultaneous partitioning and purification - Bhavsar, Kavita P.; Kumar, V. Ravi; Khire, Jayant Malhar (Process Biochemistry, 2012)
The application of single step aqueous two-phase extraction (ATPE) for the downstream processing of phytase from Aspergillus niger NCIM 563, produced under solid state fermentation, has been studied and compared with the traditional multi-step procedure involving salt precipitation and column chromatography. High phytase recovery (98.5%) within a short time (3 h) and improved thermostability was attained by ATPE in comparison to 20% recovery in 96 h by chromatography process.The ATPE method, therefore, seems to be an interesting alternative for simultaneous partitioning and purification of phytase. The influence of system parameters; such as, phase forming salts, polymer molecular weight and system pH on the partitioning behavior of phytase was evaluated. The ATPE system consisting of combination of polyethylene glycol (PEG) 6000 and 8000(10.5%) and sodium citrate (20.5%) resulted in one-sided partitioning of phytase in bottom phase with a purification factor of 2.5. This is the first report on phytase purification using liquid-liquid extraction and the results are likely to be beneficial in the poultry feed industry. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aspergillus niger; liquid-liquid extraction; Phytase; Polyethylene glycol; Purification

Combinatorial approach of statistical optimization and mutagenesis for improved production of acidic phytase by Aspergillus niger NCIM 563 under submerged fermentation condition - Bhavsar, Kavita P.; Gujar, P.; Shah, P.; Kumar, V. Ravi; Khire, Jayant Malhar (Applied Microbiology and Biotechnology, 2013)
Combination of statistical optimization and mutagenesis to isolate hypersecretory strains is studied to maximize phytase production from Aspergillus niger NCIM 563 under submerged fermentation. The overall results obtained show a remarkable 5.98-fold improvement in phytase production rates when compared to that using basal medium. Optimization of culture conditions from parent strain is studied first by the Plackett-Burman technique to evaluate the effects of 11 variables for phytase production. The results showed that glucose, MgSO4, KCl, incubation period, and MnSO4 are the most significant variables affecting enzyme production. Further optimization in these variables, using a central composite design technique, resulted in 3.74-fold increase in the yield of phytase production to 254,500 U/l when compared with the activity observed with basal media (68,000 U/l) in shake flask. Our experiments show that the phytase from A. niger NCIM 563 exhibits desirable activity in simulated gastric fluid conditions with low pH and also improved thermostability when compared to commercial phytase. The improved yield demonstrates the potential applicability of phytase enzyme as a source of phytase supplement for phosphorus nutrition and environmental protection in animal feed industry. Physical and chemical mutagenesis experiments were carried out in parallel to isolate hypersecretory mutants that could possibly further enhance the enzyme production. Using optimized media conditions of the parent strain, our results show that mutant strain A. niger NCIM 1359 increased the phytase activity by another 1.6-fold to 407,200 U/l.
Keywords: Animal feed; Aspergillus niger; Mutagenesis; Phytase; Statistical optimization

Effect of phytase from aspergillus niger on plant growth and mineral assimilation in wheat (Triticum aestivum Linn.) and its potential for use as a soil amendment - Gujar, Pradnya D.; Bhavsar, Kavita P.; Khire, Jayant Malhar (Journal of the Science of Food and Agriculture, 2013)
Background Extensive use of non-replenishable phosphate reserves as phosphate supplements in agriculture and animal feed poses a threat for environmental pollution and necessitated a search for alternative phosphate sources. Unlocking the phytate phosphorus using microbial phytase can provide an ecofriendly solution in agriculture. The aim of the present work was to evaluate the effect of phytase from Aspergillus niger NCIM 563 in degradation of phytate phosphorus to benefit plant nutrition and soil amendment in comparison with chemical fertilizers. Results An enzyme dose of 12 IU was sufficient to hydrolyze phytate and increase assimilation of phosphorus by about 74%. Phytase supplementation leads to increase in shoot:total length ratio by about 200%, indicating its growth-promoting effect. Consistency in phytase-induced growth was reflected at pot and tray levels, wherein shoot:total length ratio was observed to be 2.01 and 2.12 respectively. Mineral assimilation due to phytase was more efficient as compared to chemical fertilizers, thus overcoming the constraints of practicability and economics in the agriculture industry. Phytase was efficient in reducing the phytic acid content of soil by about 30% while simultaneously increasing the phytate phosphate availability by 1.18-fold. Conclusion Phytase from A. niger showed improvement in phytate phosphorus and mineral availability. Besides a plant growth-promoting effect, reduction in use of chemical fertilizers and soil improvement could be achieved simultaneously for maintaining the sustainability of agriculture. (c) 2012 Society of Chemical Industry
Keywords: mineral assimilation; Phytase; phytate degradation; plant growth promotion; soil amendment

Phytase isozymes from aspergillus niger NCIM 563 under solid state fermentation: biochemical characterization and their correlation with submerged phytases - Bhavsar, Kavita P.; Buddhiwant, Priyanka; Soni, Sarvesh K.; Depan, Dilip; Sarkar, Sampa; Khire, Jayant Malhar (Process Biochemistry, 2013)
Aspergillus niger NCIM 563 produces dissimilar phytase isozymes under solid state and submerged fermentation conditions. Biochemical characterization and applications of phytase Phy III and Phy IV in SSF and their comparison with submerged fermentation Phy I and Phy III were studied. SSF phytases have a higher metabolic potential as compared to SmF. Phy I is tetramer and Phy II, III and IV are monomers. Phy I and IV have pH optima of 2.5 and Phy II and III have pH optima of 5.0 and 5.6, respectively. Phy I, III and IV exhibited very broad substrate specificity while Phy II was more specific for sodium phytate. SSF phytase is less thermostable as compared to SmF phytase. Phy land II show homology with other known phytases while Phy III and IV show no homology with SmF phytases and any other known phytases from the literature suggesting their unique nature. This is the first report about differences among phytase produced under SSF and SmF by A. niger and this study provides basis for explanation of the stability and catalytic differences observed for these enzymes. Exclusive biochemical characteristics and multilevel application of SSF native phytases determine their efficacy and is exceptional. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: A. niger; Isozymes; Phytase; Solid state fermentation; Submerged fermentation

Current research and future perspectives of phytase bioprocessing - Bhavsar, Kavita P.; Khire, Jayant Malhar (RSC Advances, 2014)
Phosphorus is one of nature's paradoxes as it is life's bottleneck for subsistence on earth but at same time is detrimental in surplus quantities in an aquatic environment. Phosphorus cannot be manufactured, though fortunately it can be recovered and reused. The only way to avert a supply crisis is to implement the ``3R's'' of sustainability, ``Reduce, Reuse and Recycle.'' Phytase is likely to play a critical role in the dephosphorylation of antinutritional and indigestible phytate, a phosphorus locking molecule, to digestible phosphorus, calcium and other mineral nutrients in the coming years. Hence, efforts are required to produce cost effective phytase with fast upstream and economic downstream processing because the current available process is expensive and time consuming. This review summarizes the present state of methods studied for phytase bioprocessing. Production, extraction and purification incur a large cost in product development. In addition, the process has several limitations such as dilute concentration of enzyme, extensive downstream procedures and treatment of generated effluents. However, these methods are currently employed due to lack of alternative methods. Thus, there is a clear need for an efficient, scalable and economical process for phytase production and bioseparation, and improvements are especially required with regard to yield, purity, and energy consumption. Perspectives for an improved bioprocess development for phytase are discussed based on our own experience and recent studies. It is argued that the optimization of production techniques, strain improvement and liquid-liquid extraction deserves more attention in the future.

Selection of phytase producing yeast strains for improved mineral mobilization and dephytinization of chickpea flour - Pable, A.; Gujar, P.; Khire, Jayant Malhar (Journal of Food Biochemistry, 2014)
Among 600 yeast isolates screened for phytase production, five (Zygosaccharomyces bisporusNCIM 3265 and 3296, Williopsis saturnusNCIM 3298, Zygosaccharomyces priorionusNCIM 3299 and Schizosaccharomyces octosporusNCIM 3297) were selected as potential phytase producers. Phytase activity was found to be cell wall associated with temperature and pH optima of 50C and 4.0, respectively. Highest phytase production was attained in cane juice medium as compared with other media used. Addition of phytase to chickpea flour significantly enhanced mineral mobilization by approximately 20-28%, 26-37% and 24-42% for Zn2+, Fe2+ and Ca2+, respectively, and decreased phytic acid content by about 75-88%.

Charge-switchable gold nanoparticles for enhanced enzymatic thermostability - Shankar, Shiv; Soni, Sarvesh K.; Daima, Hemant K.; Selvakannan, P. R.; Khire, Jayant Malhar; Bhargava, Suresh Kumar; Bansal, Vipul (Physical Chemistry Chemical Physics, 2015)
This study illustrates a facile strategy for efficient immobilization of enzymes on a metal nanoparticle surface. The strategy proposed here enables the enzymatic activity to be retained while increasing the enzyme thermostability. It is demonstrated that the use of a zwitterionic amino acid tyrosine as a reducing and capping agent to synthesise gold nanoparticles allows efficient immobilization of phytase enzyme through charge-switchable electrostatic interactions. The detailed kinetic and thermodynamic studies reveal that the proposed enzyme immobilization strategy improves the overall quality of phytase by reducing the activation energy required for substrate hydrolysis and broadening the temperature window in which immobilized enzyme is able to operate. The outcomes of this study indicate that the underlying zwitterionic nature of 20 natural amino acids along with significant variability in their isoelectric points and hydropathy indices as well the ability of some of the amino acids to reduce metal ions is likely to offer significant opportunities for tailoring nano-bio interfaces in a rational manner for a range of biological applications.

Insights into the unfolding pathway and identification of thermally sensitive regions of phytase from aspergillus niger by molecular dynamics simulations - Kumar, Kapil; Patel, Krunal; Agrawal, Dinesh C.; Khire, Jayant Malhar (Journal of Molecular Modeling, 2015)
Thermal stability is of great importance in the application of commercial phytases. Phytase A (PhyA) is a monomeric protein comprising twelve alpha-helices and ten beta-sheets. Comparative molecular dynamics (MD) simulations (at 310, 350, 400, and 500 K) revealed that the thermal stability of PhyA from Aspergillus niger (A. niger) is associated with its conformational rigidity. The most thermally sensitive regions were identified as loops 8 (residues 83-106), 10 (161174), 14 (224-230), 17 (306-331), and 24 (442-444), which are present on the surface of the protein. It was observed that solvent-exposed loops denature before or show higher flexibility than buried residues. We observed that PhyA begins to unfold at loops 8 and 14, which further extends to loop 24 at the C-terminus. The intense movement of loop 8 causes the helix H2 and beta-sheet B3 to fluctuate at high temperature. The high flexibility of the H2, H10, and H12 helices at high temperature resulted in complete denaturation. The high mobility of loop 14 easily transfers to the adjacent helices H7, H8, and H9, which fluctuate and partially unfold at high temperature (500 K). It was also observed that the salt bridges Asp110-Lys149, Asp205-Lys277, Asp335-Arg136, Asp416-Arg420, and Glu387-Arg400 are important influences on the structural stability but not the thermostability, as the lengths of these salt bridges did not increase with rising temperature. The salt bridges Glu125-Arg163, Asp299-Arg136, Asp266-Arg219, Asp339-Lys278, Asp335-Arg136, and Asp424-Arg428 are all important for thermostability, as the lengths of these bridges increased dramatically with increasing temperature. Here, for the first time, we have computationally identified the thermolabile regions of PhyA, and this information could be used to engineer novel thermostable phytases. Numerous homologous phytases of fungal as well as bacterial origin are known, and these homologs show high sequence similarity. Our findings could prove useful in attempts to increase the thermostability of homologous phytases via protein engineering.
Keywords: Conformational dynamics; Molecular dynamics simulations; PhytaseA; Structurally weak regions; Thermostability